Molecular genetic evidence for the human settlement of the Pacific: analysis of mitochondrial DNA, Y chromosome and HLA markers. - Hagelberg, E (1999)
Present-day Pacific islanders are thought to be the descendants of Neolithic agriculturalists who expanded from island South-east Asia several thousand years ago. They speak languages belonging to the Austronesian language family, spoken today in an area spanning half of the circumference of the world, from Madagascar to Easter Island, and from Taiwan to New Zealand. To investigate the genetic affinities of the Austronesian-speaking peoples, we analysed mitochondrial DNA, HLA and Y-chromosome polymorphisms in individuals from eight geographical locations in Asia and the Pacific (China, Taiwan, Java, New Guinea highlands, New Guinea coast, Trobriand Islands, New Britain and Western Samoa). Our results show that the demographic expansion of the Austronesians has left a genetic footprint. However, there is no simple correlation between languages and genes in the Pacific.